Evaluation of epidemiological, clinical, and microbiological features of definite infective endocarditis - Faraji, Reza (GMS Hygiene and Infection Control, 2017)
Background: Infective endocarditis (IE) is a microbial infection of heart valves and its endothelial lining which is considered as a life-threatening disorder. This study evaluated the epidemiological, clinical, and microbiological features of IE at the Cardiovascular Research Center in Yazd, Iran. Methods: The cross-sectional study was conducted on 20 patients diagnosed with definite IE on the basis of Duke’s criteria hospitalized for one year in the Cardiovascular Research Center in Yazd, Iran, from January 2015 to December 2015. Demographic information, clinical, laboratory, and microbiological findings, and also trans-esophageal echocardiography (TEE) of each patient were recorded and assessed. The collected data were analyzed using SPSS 16. Results: The mean age of the patients under study was 45±16 years with most of the afflicted patients (60%) being male. Most cases (70%) of IE were observed in the warm seasons (spring and summer). The most common clinical sign (80%) was fever. TEE was positive for all (100%) patients, and vegetation was seen in all patients. The nosocomial mortality rate was zero. However, 14 (70%) patients underwent surgical treatment. The valves afflicted with IE were: the mitral valve (40%), the aortic valve (35%), and the tricuspid valve (25%), respectively. 4 patients (20%) had a positive history of IE. Blood culture test was positive only in 1 case and the isolated microorganism belonged to the viridans group streptococci. Conclusion: Despite the one-year high prevalence of IE in this study, the nosocomial mortality rate was not high and was reported to be nil under surgical and antimicrobial therapy.